Menopause - Subedi, Durga (Journal of Nursing Education of Nepal, 2011)
Menopause is defined as the permanent cessation of menses resulting from reduced ovarian hormone secretion that occurs naturally or is induced by surgery. Natural menopause is recognized after 12 months of amenorrhea that is not associated with a pathologic cause. The average age of menopause worldwide is 51 years. The typical age range for the occurring is between the ages of 45 to 55.The average age of menopause varies according to geographic location is different in different countries and societies. In developing countries, it is about 1 to 2 years lower than the developed countries. In Nepal, the average age for menopause is 49 to 50 in Kathmandu valley and 47 in other rural areas. In the western world, last period ever occurring between the ages of 55 to 60 is known as late menopause and early menopause is defined as having one’s final period, somewhere between the ages of 45 to 50. A hot flush, perspiration, night sweats, vaginal dryness, sleep disturbance, mood symptoms, somatic complaints, uterine bleeding, and sexual dysfunction are common. Specific treatment for menopausal symptoms determined by the physician based on age, overall health and medical history, and current symptoms. Several therapies that help to manage the symptoms often associated with menopause including hormone replacement therapy involve the administration of a combination of the hormones estrogen and progesterone or the administration of estrogen alone.